Creativity in museum practice - Norris, Linda. (Left Coast Press, 2014)
"With this book museum professionals can learn how to unleash creative potential throughout their institution. Drawing from a wide range of research on creativity as well as insights from today's most creative museum leaders, the authors present at a set of practical principles about how museum workers at any level--not just those in "creative positions"--can make a place for creativity in their daily practice. Replete with creativity exercises and stories from the field, they guide readers in developing an internal culture of creative learning, as well as delivering increased value to museum audiences"--